Cioran, skepticism and style election - Abad, Alfredo (Estudios de Filosofía, 2019)
Cioran introduces two fairly clear stylistic choices in his work. One focused on lyricism where poetry has a very broad influence, and another focused on a critical language where he tries to detach himself from lyrical and poetic traces. The paper explores these two aspects and points out their particularities, their possible antagonisms and the reasons that motivate their use in the work of the Romanian author through its skeptical imprint.